A colorimetric sensor for detecting thiourea based on inhibiting peroxidase-like activity of gold–platinum nanoparticles. Issue 8 (12th February 2021) - Zhao, Yuqi; Fu, Qingjie; Cui, Xiaoqian; Chi, Hui; Lu, Yongzhuang; Liu, Xiaoli; Yu, Miao; Fei, Qiang; Feng, Guodong; Shan, Hongyan; Huan, Yanfu
Abstract : The sensor is based on the peroxidase-like activity of Au@PtNPs. Thiourea can quickly be detected by the color change of the solution. The method was applied to the determination of thiourea in practical samples. Abstract : In this study, gold–platinum nanoparticles (Au@PtNPs) with peroxidase-like activity were synthesized. In the absence of thiourea (TU), the Au@PtNPs can catalyze the decomposition of hydrogen peroxide, and oxidize 3, 3′, 5, 5′-tetramethylbenzidine dihydrochloride (TMB, colorless) into oxidized 3, 3′, 5, 5′-tetramethylbenzidine dihydrochloride (oxTMB, blue). The peroxidase-like activity of the Au@PtNPs is inhibited in the presence of TU, and TMB cannot be oxidized to oxTMB effectively, and no blue color could be observed. Based on this finding, a novel colorimetric sensor for detecting TU is proposed. The absorbance response curve showed a good linearity for the concentration of TU in the range of 10 nmol L −1 to 10 μmol L −1 with a correlation coefficient of R 2 = 0.999, and the limit of detection is 9.57 nmol L −1 . The colorimetric sensor possesses excellent selectivity, anti-interference ability, and application value in actual samples.